Towards Assimilating the Damage Conditions in Administrative Responsibility for the Case of Environmental Damage - Maifi, Kamel (Journal of Legal Studies and Researches, 2022)
Environmental damage is one of the modern forms of damage. Since the administration is obligated to redress the damage resulting from its multiple activities, the effective protection of the environment cannot be achieved only if the administrative judge takes in charge the development administrative responsibility rules to assimilate the specificity of environmental damage.